The Real Time Big Data Processing Framework: Advantages and Limitations - Gurusamy, Vairaprakash; Kannan, S; Nandhini, K (International Journal of Computer Sciences and Engineering, 2025)
Big data is a blanket term for the non-traditional strategies and technologies needed to gather, organize, process, and gather insights from large datasets. While the problem of working with data that exceeds the computing power or storage of a single computer is not new, the pervasiveness, scale, and value of this type of computing have greatly expanded in recent years. In this paper, we will take a look at one of the essential components of a big data system: processing frameworks. Processing frameworks compute over the data in the system, either by reading from non-volatile storage or as it is ingested into the system. Computing over data is the process of extracting information and insight from large quantities of individual data points.